Biocide treatment for mosquito control increases CH4 emissions in floodplain pond mesocosms - Ganglo, Caroline; Manfrin, Alessandro; Mendoza-Lera, Clara; Lorke, Andreas (Frontiers in Water, 2022)
Small standing water emits a large amount of methane into the atmosphere. It has been found that chironomid larvae which dwell in sediment at their larval stage, reduce methane production and increase methane oxidation by enhancing oxygen transport into the sediment. Thus chironomids' presence may reduce methane emissions. We performed our study in twelve floodplain mesocosms to evaluate to what extent chironomids larvae influence methane cycle in aquatic systems. Six of the floodplain mesocosms were treated with mosquito biocide to reduce chironomids' abundance, whereas the six other floodplain mesocosms were not treated. We measured methane emissions, concentration, and oxidation in the twelve floodplains mesocosms during spring, summer, autumn, and winter. Our results show that the methane emissions in treated floodplain mesocosms with biocide are much higher than in non-treated floodplain mesocosms. We also observed large seasonal variations in methane emissions and methane concentrations. We suggest that the reduction in chironomids abundance promoted methane production in sediment due to a lack of oxygen transport. The findings suggest that by altering the chironomid abundance, mosquito biocide may affect methane biogeochemistry, highlighting the underappreciated role of invertebrates in biogeochemical cycling.